Age‐specific risk factors for incident disability in activities of daily living among middle‐aged and elderly community‐dwelling Japanese women during an 8–9‐year follow up: The Hizen‐Oshima study. Issue 7 (12th July 2016) - Okabe, Takuhiro; Abe, Yasuyo; Tomita, Yoshihito; Mizukami, Satoshi; Kanagae, Mitsuo; Arima, Kazuhiko; Nishimura, Takayuki; Tsujimoto, Ritsu; Tanaka, Natsumi; Goto, Hisashi; Horiguchi, Itsuko; Aoyagi, Kiyoshi
Abstract : Aim: The purposes of the present study were to investigate risk factors for incident disability in activities of daily living (ADL) among middle‐aged and older women, and to determine whether there are differences in risk factors according to age groups. Methods: The participants were 264 Japanese women aged 40 years and older. A self‐administered questionnaire was used to survey participants about difficulty in carrying out selected basic and instrumental ADL at baseline and at follow up. ADL disability was defined as difficulty carrying out three or more ADL. Information on knee joint or back pain and comorbidities (heart disease, lung disease, stroke or diabetes mellitus) was obtained using a self‐administered questionnaire at baseline. Physical performance measurements (grip strength, chair stand time, rapid walking speed and functional reach) were also carried out at baseline. Results: The prevalence of incident ADL disability was 44 (27.5%) in women aged 40–64 years, and 57 (54.8%) in women aged ≥65 years ( P  < 0.001). Multiple logistic regression analysis showed that decreased grip strength and having pain were significantly associated with a higher risk for incident ADL disability among women aged 40–64 years. For women aged ≥65 years, decreased rapid walking speed, having a comorbidity and having pain were associated with incident ADL disability. Conclusions: The present study showed that a different set of risk factors was associated with incident ADL disability among women aged 40–64 years and women aged ≥65 years. Age‐specific screening and intervention strategies are necessary for effective prevention of incident ADL disability.Geriatr Gerontol Int 2017; 17: 1096–1101 .